The Rate of Histamine Degradation by Diamine Oxidase Is Compromised by Other Biogenic Amines - Sánchez-Pérez, Sònia; Comas-Basté, Oriol; Costa-Catala, Judit; Iduriaga-Platero, Irache; Veciana-Nogués, M. Teresa; Vidal-Carou, M. Carmen; Latorre-Moratalla, M. Luz (Frontiers in Nutrition, 2022)
Nowadays, certain uncertainties related to the onset of histamine adverse effects remain unsolved and still require further research. Questions still to be resolved include the wide range of doses at which dietary histamine may trigger symptoms of intoxication (100–10,000 mg/kg) or the appearance of symptoms of histamine intolerance after the consumption of foods presumable without histamine. It seems feasible that other amines, by acting as competitive substrates, could interfere with histamine degradation by the intestinal enzyme diamine oxidase (DAO). Therefore, the aim of this study was to elucidate the interference of different amines on the rate of histamine degradation by DAO. A series of in vitro enzymatic assays were performed using histamine as the reaction substrate combined with different proportions of putrescine, cadaverine, tyramine, spermidine, and spermine (1:0.25, 1:1, 1:4, 1:20). Putrescine and cadaverine significantly delayed histamine degradation at all tested concentrations (p < 0.001). The greatest effect was observed when putrescine or cadaverine concentrations were 20-fold higher than that of histamine, its degradation being reduced by 70 and 80%, respectively, compared to histamine alone (28.16 ± 1.0 mU). In contrast, tyramine, spermidine and spermine significantly inhibited the histamine degradation rate only at the highest concentration (1:20), reducing it by 32–45%. These results demonstrate that other biogenic amines interfere with histamine metabolization by DAO in vitro, the extent depending on the substrate. These findings could explain why susceptibility to dietary histamine is so variable and account for the discrepancies in the scientific databases regarding the amount of histamine that triggers adverse health effects.